Trade Credit and the Effect of Macro-Financial Shocks : Evidence From U.S. Panel Data - Kim, Yungsan (IMF Working Papers; Working Paper ;, 2003)
Many studies examine why firms are financed by their suppliers, but few empirical studies look at the macroeconomic implications of such financial arrangements. Using disaggregated panel data, we examine how firms extend and use trade credit. We find that, controlling for the transactions or asset management motive, both accounts payable and receivable increase with tighter policy, implying that trade credit helps firms absorb the effect of a credit contraction. A comparison of S and P 500 firms with smaller firms, however, provides no evidence that when policy is tightened, large firms play the role of credit suppliers more actively than small firms.